Role Of School Facilities And Infrastructure On Performance Of Senior High School Teacher - Wa Ode Riniati; Rinovian Rais; Raudya Setya Wismoko Putri; Firman Azis; Gamar Al Haddar (Departement of Mathematics Education, 2023)
Several previous studies with the main problem of teacher performance in terms of infrastructure and work environment factors generally used regression analysis techniques, which only studied the direct effect of infrastructure and work environment on teacher performance. The novelty of this research is the development of instruments using the Structural Equation Modeling (SEM) measurement model, namely developing constructs from performance variables, infrastructure and work environment, through theoretical validation through experts and empirical validation using Confirmatory Factor Analysis (CFA) techniques. Seeing the important role of infrastructure and work environment on teacher performance, the purpose of this study was to determine the effect of infrastructure and work environment on teacher performance. This study used a quantitative approach using survey methods with the analytical techniques used, namely instrument development using the Structural Equation Modeling (SEM) measurement model, and multiple linear regression. The population in this study were high school teachers throughout Tangerang. Respondents were taken based on 20 schools in Tangerang and each school took several samples, and it was obtained as a whole that the sample obtained was 200 respondents. The result of this study is all independent variables has a positive and significant effect toward dependent variable.